2013
DOI: 10.3233/npm-1371813
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for the development of necrotizing enterocolitis: A case-control study

Abstract: AIM: To determine risk or protective factors for the development of necrotizing enterocolitis in very low birth weight infants. METHODS: This retrospective case-control study was conducted at La Paz University Hospital including infants with a birth weight of <1500 g for three years. Cases with confirmed diagnosis of necrotizing enterocolitis were evaluated; each one was paired with a control infant of the same gestational age. Statistical analysis included unadjusted and multivariable analyses. RESULTS: A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
3
3
0
Order By: Relevance
“…When considering possible risk factors, we did not find an association between NEC and gestational age, birth weight, sex, Apgar scores at one and five minutes of life, RDS (plus surfactant) or PDA (plus ibuprofen), which was consistent with the similar study of Martin et al [22]. On the other hand, in a study, which had a sample three times bigger than ours (111 cases and 222 controls) PDA and treatment with indomethacin were found to differ significantly between cases and controls [21].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…When considering possible risk factors, we did not find an association between NEC and gestational age, birth weight, sex, Apgar scores at one and five minutes of life, RDS (plus surfactant) or PDA (plus ibuprofen), which was consistent with the similar study of Martin et al [22]. On the other hand, in a study, which had a sample three times bigger than ours (111 cases and 222 controls) PDA and treatment with indomethacin were found to differ significantly between cases and controls [21].…”
Section: Discussionsupporting
confidence: 92%
“…We found that all three variables describing transfusion before NEC correlated with NEC compared very similarly to some previous studies. Transfusion as a nominal variable had an adjusted odds ratio (OR) of 3.0 (95% CI 1.1, 8.0, p = 0.034), which is almost identical to that reported by Wan-Huen et al [19] For transfusion as an ordinal variable, the unadjusted OR was 1.5 (95% CI 1.0, 2.2, p = 0.04), which is the same as in Martin et al [22] and the adjusted OR (1.6, 95% CI 1.0, 2,5, p = 0.056), although of borderline statistical significance, is comparable to the report of Bak et al [20] Moreover, in our study the volume of PRBC transfused also significantly correlated with increased odds of NEC (adjusted OR 1.04, 95% CI 1.0, 1.1, p = 0.043).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…However, some studies suggest transfusion may be an aggravating factor. [25][26][27] But this may be because of the presence of anemia and not the transfusion aggravating the NEC. 28 Pre-terms frequently require transfusion to improve oxygen delivery to the vital organs during the crucial phase of growth and development, but there are still controversies regarding optimal management of anemia in pre-term neonates.…”
Section: Methodsmentioning
confidence: 99%